(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Attention is drawn to a putative WISC anomaly, specific to the case of Intellectual Disability (ID) IQ assessment. With ID, at best the WISC-IV Picture Concepts (PCn) is not a consistent part of the underlying “ability” represented by Perceptual Reasoning Index (PRI) factor, while at worst the PCn score may be “wrong”. This worst case situation is marked by a “very high PCn score” in an otherwise low profile and this outcome awaits a better interpretation which would be meaningful to the target child with Intellectual Disability. The literature relating to PCn scores in cases of “intellectually different” cohorts shows conflicting published evidence that the sub-test may be either generally lower than the cohort average, or generally above that average, for example in cases of Autism. The present paper proposes that the broad explanation for the PCn anomaly is explained by deriving an answer to each item from a focus on single-feature solution rather than an integrative approach. Future research may clarify the frequency and the meaning of this issue, while the present paper raises a caution in the “standard” interpretation of intellectual disability IQ profiles.